ANALISIS KUALITAS PELAYANAN PEMBUATAN SERTIFIKAT TANAH DI KANTOR BADAN PERTANAHAN NASIONAL KABUPATEN SEMARANG - Widuri, Anissa Ratna; Maesaroh, Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
Research is called analysis the quality of the process of land certificates at the office of the national land kabupaten semarang. During this according to persepektif the community that to process the land certificate cost money expensive, a long time, procedural complicated and tortuous so that it result less than optimal. The purpose of this research is to analyze the quality of the process of land certificates granted from the bpn to the community. This research using design the qualitative study with the approach descriptive. The research results show that BPN kabupaten semarang in the delivery of has not been well. To analyze the quality of the process of land certificates writer both five dimensions according to berries zeithmal and parasuraman: tangible, reliability, responsiveness, assurance and empathy. Of five dimensions subjects there are still some obstacles that is in dimension reliability indicated of not all officers can operate computer well, responsiveness relating to less cermatnya in the check file an applicant, and assurance indicated related issuing certificates who often more than the target of time that had been determined. It is suggested that land office kabupaten semarang increase training computerized, implement the orderly administration and socialization intensively to the kecamatan, urban village and the representatives of the community to the land registration in kabupaten semarang increased.